2015
DOI: 10.4018/ijmtie.2015070103
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cocaine Metabolite and Liver CYP450 3A4 Isoenzyme Levels as Indicators of Cocaine Dependence in Rats Treated with Nutritional Supplements

Abstract: The effects that chronic cocaine administration (CCA) have on craving, cocaine metabolite concentrations and cytochrome P450 3A4 isoenzyme (CYP450 3A4) activities in Sprague-Dawley rats following the administration of Salako Nutritional Supplements (SNS) were examined. Five groups of fifty rats were used to assess the effect of the SNS following CCA. Craving was analyzed for each rat using a Conditioned Place Preference protocol. Blood samples were obtained at regular intervals and used to measure cocaine plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These findings are also consistent with the sex difference we noted from daily health observations where severe health complications led to the removal of both males and females in the control-chow group; whereas, among SMAASH-C treated rats, only females developed severe health complications indicating that SMAASH-C treatment may improve the overall health of males, but not females, during cocaine abstinence. A previous study reported that SMAASH-C offers protective effects against chronic cocaine exposure by increasing plasma clearance of cocaine and its toxic metabolites through increasing the activity of the liver enzyme CYP450 [ 18 ]. One caveat is that while both males and females were included in this previous study, sex was not considered so it is still possible that effects on liver activity were driven by males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are also consistent with the sex difference we noted from daily health observations where severe health complications led to the removal of both males and females in the control-chow group; whereas, among SMAASH-C treated rats, only females developed severe health complications indicating that SMAASH-C treatment may improve the overall health of males, but not females, during cocaine abstinence. A previous study reported that SMAASH-C offers protective effects against chronic cocaine exposure by increasing plasma clearance of cocaine and its toxic metabolites through increasing the activity of the liver enzyme CYP450 [ 18 ]. One caveat is that while both males and females were included in this previous study, sex was not considered so it is still possible that effects on liver activity were driven by males.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal reports and open label observational data from patients indicate that oral SMAASH-C (0.1-0.4 g/kg/day; 6-12 months) treatment during abstinence improves markers of general health (e.g., one patient with co-morbid AIDS-related herpes simplex virus infection reporting marked improvement in viral symptoms) and reduces drug-craving, frequency of relapse, and withdrawal symptoms. Results from subsequent preclinical studies were also promising and showed that chronic SMAASH-C treatment (oral, 0.04-0.12 g/kg, 8 weeks) markedly and selectively reduced cocaine- and amphetamine-induced conditioned place preference and markers of drug-induced toxicity in male and female rats [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritionally supplemented animals were proportionally fed a combination of the named component, at 0.123 g/day, 0.123 g/day and 0.0408 g/day, respectively, over a period of 8 weeks. These doses were calculated based on a 350 g rat, after proportions previously used in other studies for administration to a 75 kg man were scaled down [11].…”
Section: The Conditioned Place Preference Paradigmmentioning
confidence: 99%